Continental climate in the East Siberian Arctic during the last interglacial: Implications from palaeobotanical records. - Kienast, Frank; Schirrmeister, Lutz (PANGAEA, 2017)
To evaluate the consequences of possible future climate changes and to identify the main climate drivers in high latitudes, the vegetation and climate in the East Siberian Arctic during the last interglacial are reconstructed and compared with Holocene conditions. Plant macrofossils from permafrost deposits on Bol'shoy Lyakhovsky Island, New Siberian Archipelago, in the Russian Arctic revealed the existence of a shrubland dominated by Duschekia fruticosa, Betula nana and Ledum palustre and interspersed with lakes and grasslands during the last interglacial. The reconstructed vegetation differs fundamentally from the high arctic tundra that exists in this region today, but resembles an open variant of subarctic shrub tundra as occurring near the tree line about 350 km southwest of the study site. Such difference in the plant cover implies that, during the last interglacial, the mean summer temperature was considerably higher, the growing season was longer, and soils outside the range of thermokarst depressions were drier than today. Our pollen-based climatic reconstruction suggests a mean temperature of the warmest month (MTWA) range of 9-14.5 °C during the warmest interval of the last interglacial. The reconstruction from plant macrofossils, representing more local environments, reached MTWA values above 12.5 °C in contrast to today's 2.8 °C. We explain this contrast in summer temperature and soil moisture with a combination of summer insolation higher than present and climatic continentality in arctic Yakutia stronger than present as result of a considerably less inundated Laptev Shelf during the last interglacial.
Plant macrofossil records from permafrost deposits of the Bol'shoy Lyakhovsky Island (New Siberian Archipelago)
Keywords: Agrostis sp.; Alnus fruticosa; Alopecurus sp.; Alyssum biovulatum; Androsace septentrionalis; Area/locality; Artemisia sp.; Asteraceae sp.; AWI_PerDyn; Batrachium sp.; Betulaceae; Betula fruticosa; Betula nana; Betula sp.; Boschniakia rossica; Brassicaceae sp.; Calamagrostis sp.; Callitriche hermaphroditica; Caltha palustris; Carex aquatilis; Carex cf. sect. Temnemis; Carex duriuscula; Carex sect. Phacocystis; Carex sp.; Carex supina; Caryophyllaceae sp.; Cerastium beeringianum; Cerastium cf. regelii; Cerastium jenissejense; cf. Corydalis sp.; cf. Lesquerella arctica; cf. Saxifraga hieracifolia; Chara sp.; Chenopodiaceae sp.; Chenopodium sp.; Chrysosplenium alternifolium; Comarum palustre; Cyperaceae sp.; Deschampsia sp.; Descurainia sophioides; Draba sp.; Dryas octopetala; ELEVATION; Empetrum nigrum; Epilobium davuricum; Epilobium palustre; Eriophorum angustifolium; Eriophorum brachyantherum; Eriophorum cf. gracile; Eriophorum scheuchzeri; Eriophorum sp.; Eutrema edwardsii; Fabaceae sp.; Festuca sp.; Gastrolychnis involucrata; Gastrolychnis violascens; Hippuris vulgaris; Juncus castanaeus; Kobresia bellardii; Ledum palustre ssp. decumbens; Lloydia serotina; Luzula cf.wahlenbergii; Luzula confusa; Lya_1999; Lya_1999_L11; Lya_1999_R17; Lya_1999_R22; Lya_1999_R35; Lya_1999_R6; Lya_1999_R8+50; Lyakhovsky Islands; Menyanthes trifoliata; Minuartia arctica; Minuartia rubella; Moehringia laterifolia; MULT; Myosotis sp.; Myriophyllum spicatum; Oxycoccus microcarpus; Oxyria digyna; Papaver sect. Scapiflora; Parnassia palustris; Permafrost Research (Periglacial Dynamics) @ AWI; Poaceae sp.; Poa sp.; Polygonum viviparum; Potamogeton sp.; Potamogeton vaginatus; Potentilla arenosa; Potentilla hyparctica; Potentilla nivea; Potentilla sp.; Potentilla stipularis; Primulaceae sp.; Puccinelia sp.; Puccinellia distans; Ranunculus borealis; Ranunculus cf. pygmaeus; Ranunculus cf. reptans; Ranunculus hyperboreus